Kemampuan Penalaran Matematis Siswa Berdasarkan Gender dengan Pendekatan STEM pada Modul Matematika - Kartika Pratiwi; Saiful Bahri; Dona Dinda Pratiwi (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
This research aims to find out the implementation of STEM module based on ICARE learning model approach regarding to the differences gender in mathematics abilities. This research is a Quasi Experimental Design with a 2 × 2 factorial design. The sample of this research was 2 clasess those were VII C and VII F, each classes consisted of 30 students, which 35 male students and 25 female students. To conduct the data, the researcher used test to control class and experiment class, then analyzed the data using SPSS 25.0. Based on the results of the two-way analysis of variance with different cells, showed that the ICARE learning model assisted by the module with the STEM approach and the PBL model assisted by students' worksheet on mathematical reasoning abilities, (gender differences in mathematical reasoning abilities, there is no interaction with the ICARE assisted learning model module with the STEM approach and PBL model assisted by students' worksheet with gender differences on mathematical reasoning abilities.